Estimation of the Brazilian consumer demand system - Seki Asano; Eduardo P. S. Fiuza (Institute for Applied Economic Research (ipea), 2015)
In this study we estimate the Brazilian consumer demand system through family expenditure data, which cover all consumption categories. The model is estimated from family-level expenditures on seven consumption categories, and a new set of regional cost-of-living indexes. The sources for expenditures are the national expenditure surveys conducted in 1986/87 and 1995/96, which collected data from 11 metropolitan areas. Corresponding price indexes were constructed from detailed commodity prices, also from each metropolitan area. The salient features of our study are: a) price variations come from both time and regional differences, which allows us to estimate price elasticities with high precision; b) we have large variations in income (total expenditures) which is rarely available in aggregated data; and c) we can control for time specific factors by exploiting the panel structure of the data set.
Keywords: C33; C81; D12; 330; Consumer demand System; Almost Ideal Demand System; Brazilian family expenditures